2020
DOI: 10.3920/wmj2020.2567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deoxynivalenol and fumonisins fed in combination on beef cattle: health and performance indices

Abstract: Interactions between livestock management practices and toxicological outcomes of mycotoxin exposure may explain the range of tolerable toxin levels reported for various species. In the current study, we investigated the effect of concurrent mycotoxin exposure with a high starch diet in 12 beef steers in a partial cross-over experiment using a 21-day treatment period, followed by a 14-day clearance. During the treatment period, animals were assigned to one of two diets: a low mycotoxin control total mixed rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…Taken together, these results suggest that the CD4:CD8 ratio could be a candidate biomarker of early DON exposure in beef cattle, which may be attenuated by co-occurring FUM toxicity. These results support previous literature citing the sensitivity of lymphocytes to this class of toxins [ 12 , 13 , 24 ]. Additional validation studies with a larger number of samples across more stratified doses are warranted to further explore this possibility.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Taken together, these results suggest that the CD4:CD8 ratio could be a candidate biomarker of early DON exposure in beef cattle, which may be attenuated by co-occurring FUM toxicity. These results support previous literature citing the sensitivity of lymphocytes to this class of toxins [ 12 , 13 , 24 ]. Additional validation studies with a larger number of samples across more stratified doses are warranted to further explore this possibility.…”
Section: Resultssupporting
confidence: 92%
“…Decreased proliferation of CD4 − CD8 + , CD4 + CD8- and CD4 + CD8 + porcine T cells with DON exposure at levels greater than 0.4 µM and reduced proliferation of peripheral blood mononuclear cells (PBMCs, primarily lymphocytes of unknown CD4/8 phenotypes) in cattle at DON levels as low as 0.21 µM have been observed [ 13 , 25 ]. While true absorption of DON in steers of this study is unknown, even a conservative estimate of blood volume (425 kg average body weight, 9 kg TMR intake/day [ 24 ]) would conclude that cytotoxic DON levels are reported to perturb PBMCs from this species [ 13 ] would be attainable only with a high absorption and distribution of the parent toxin. A previous work by Taranu (2010) reported that FUM was a very poor inhibitor of PBMC proliferation; however, the combined effects of DON and FUM on PBMCs in this species have not been explored.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations